PENINGKATAN KETERAMPILAN BERCERITA DENGAN MENGGUNAKAN MEDIA BONEKA TANGAN KELAS IV SEKOLAH DASAR - purbasyafin, ajeng aprillia; Sukma, Hanum Hanifa (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2020)
The aim of the study was to improve storytelling skills through hand puppets and solve the steps to improve storytelling skills with puppets of grade IV students at SDN 05 Bojongbata. This type of research is classroom action research, with Kemmis and Mc. Taggart. The research subjects were grade IV students who participated in 35 students and the object of the study was the student learning outcomes. Data collection techniques using the method of observation, testing and documentation. The data analysis technique used descriptive quantitative data analysis techniques. The results showed an increase in the results of the research on storytelling skills in students. The results showed the first cycle to get an average of 73.56% learning outcomes with completeness, an increase in the second cycle to get an average of 85.71% learning outcomes with completeness. Based on the results of the study, using puppet media can improve the skills of students in grade IV SDN 05 Bojongbata.